An analysis of heavy metals contamination and estimating the daily intakes of vegetables from Uganda. (22nd January 2021) - Kasozi, Keneth Iceland; Otim, Eric Oloya; Ninsiima, Herbert Izo; Zirintunda, Gerald; Tamale, Andrew; Ekou, Justin; Musoke, Grace Henry; Muyinda, Robert; Matama, Kevin; Mujinya, Regan; Matovu, Henry; Ssempijja, Fred; et al.
Background: Environmental contamination with elevated levels of copper (Cu), cobalt (Co), iron (Fe), zinc (Zn), lead (Pb), chromium (Cr 6+ ), cadmium (Cd), and nickel (Ni)—all states of which are found in Uganda—raises health risk to the public. Pb, Cr 6+, Cd, and Ni for instance are generally considered nonessential to cellular functions, notwithstanding the importance of the oxidative state of the metals in bioavailability. As such, we aimed in this study (i) to evaluate heavy metal concentrations in four vegetables from a typical open-air market in Uganda, (ii) to assess the safety of consuming these vegetables against the World Health Organization (WHO) recommended limits of heavy metals consumption, and (iii) to formulate a model of estimated daily intake (EDI) among consumers in the country. Methods: This was a cross-sectional study conducted in five georeferenced markets of Bushenyi district in January 2020. Amaranthus, cabbages, scarlet eggplants, and tomatoes were collected from open markets, processed, and analyzed by atomic absorption spectrometry. Modeled EDI, principal component (PCA) and cluster analysis (CA) were conducted to identify relationships in the samples. Results: The levels of essential elements in the four vegetables were found to fall from Co > Cu > Fe > Zn. Those of non-essential metals were significantly higher and followed the pattern Cd > Cr > Pb > Ni. The highest EDI values were those of Cu in scarlet eggplants, Zn in amaranthus, Fe in amaranthus, Co in amaranthus, Pb in cabbages, total Cr in scarlet eggplant, Cd in cabbages and tomatoes, and Ni in cabbages. In comparison to international limits, EDIs for Zn, Cu, Co and Fe were low while Ni in cabbages were high. PCA showed high variations in scarlet eggplant and amaranthus. The study vegetables were found to be related with each other, not according to the location of the markets from where they were obtained, but according to their species by CA. Conclusion: The presence of non-essential elements above WHO limits raises policy challenges for the consumption and marketing of vegetables in the study area. Furthermore, low EDIs of essential elements in the vegetables create demand for nutritious foods to promote healthy communities.